2018
DOI: 10.1590/1413-785220182602182353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Dose Vitamin C and Hyaluronic Acid on Tendon Healing

Abstract: Objective:To assess the histopathologic and biomechanical effects of hyaluronic acid (HA) and high-dose vitamin C (VC) on rat Achilles tendon healing. Methods:Forty-eight Sprague-Dawley rats were randomized to HA and VC and control groups with equal numbers. Each group was further divided into two subgroups to be sacrificed on Day 15 (n=8) and Day 30 (n=8). The Achilles tendons were cut and repaired. While the control rats remained untreated, HA and VC were administered after repair. The repaired tendons were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 18 publications
1
18
0
3
Order By: Relevance
“…Ele atua como cofator na síntese de colágeno em enzimas envolvidas na cicatrização, a lisil-oxidase é a mais notável, na qual catalisa a formação de ligações cruzadas covalentes pela formação de grupo aldeído nas moléculas de colágeno, além da função antioxidante (AGREN et al, 1990;OLIVEIRA et al, 2017). (OLIVEIRA et al, 2017) , em que ocorre em duas enzimas principais de formação do mesmo, a lisil e a prolil hidroxilases, cujos modos de ação é a catalisação dos resíduos de prolil e lisil por hidroxilação nos peptídeos de colágeno e com isso permitirá a estabilização e a biossíntese de colágeno de tripla hélice (MONTEIRO et al, 2014;DINCEL et al, 2018).…”
Section: Discussionunclassified
“…Ele atua como cofator na síntese de colágeno em enzimas envolvidas na cicatrização, a lisil-oxidase é a mais notável, na qual catalisa a formação de ligações cruzadas covalentes pela formação de grupo aldeído nas moléculas de colágeno, além da função antioxidante (AGREN et al, 1990;OLIVEIRA et al, 2017). (OLIVEIRA et al, 2017) , em que ocorre em duas enzimas principais de formação do mesmo, a lisil e a prolil hidroxilases, cujos modos de ação é a catalisação dos resíduos de prolil e lisil por hidroxilação nos peptídeos de colágeno e com isso permitirá a estabilização e a biossíntese de colágeno de tripla hélice (MONTEIRO et al, 2014;DINCEL et al, 2018).…”
Section: Discussionunclassified
“…43,44 Vitamin C potentiates tendon healing by increasing the collagen fibril diameter and the number of fibroblasts at the injured site, as well as by promoting local angiogenesis. 4 In addition, vitamin C has been shown to reduce peritendinous adhesions in an animal model. 45 Animal studies have investigated the effect of vitamin C on healing of the Achilles tendon (AT).…”
Section: Tendon Healingmentioning
confidence: 99%
“…43,44 A study by Omerğlu et al 43 tested the effect of high-dose vitamin C supplementation on AT healing in rats, and they found that vitamin C accelerated tendon healing. A study by Dincel et al 4 sought to determine the effect of high-dose vitamin C or hyaluronic acid (HA) on AT healing in rats, and they discovered that both vitamin C and HA, in isolation but more so in combination, led to higher tendon tensile strength measurements when compared to the control. 4 In 2019, Souza et al 44 reported that vitamin C led to faster AT tissue organization, better organization of the collagen network, and improved ultimate tendon functionality compared to the control in rats.…”
Section: Tendon Healingmentioning
confidence: 99%
See 2 more Smart Citations